2011
DOI: 10.1111/j.1532-849x.2011.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of an Acrylic Resin after Incorporation of an Antimicrobial Monomer

Abstract: The incorporation of MUPB affects the mechanical properties of a denture base acrylic resin; however, the only significant change was observed for flexural strength and may not be critical. Color changes were slightly higher when resin containing MUPB was immersed in wine for a prolonged time; however, the difference has debatable clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
7
36
1
3
Order By: Relevance
“…The results of this study exceeded the recommended minimum values in all experimental conditions and may not have clinical relevance. Nevertheless, the values were in agreement with results obtained in the literature for heat-polymerized resins based on polymethyl methacrylate 11,[22][23][24] . However, as pointed out above, the results must be interpreted with caution, because different performance can be obtained when these materials are under fatigue loads when in function 25) .…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study exceeded the recommended minimum values in all experimental conditions and may not have clinical relevance. Nevertheless, the values were in agreement with results obtained in the literature for heat-polymerized resins based on polymethyl methacrylate 11,[22][23][24] . However, as pointed out above, the results must be interpreted with caution, because different performance can be obtained when these materials are under fatigue loads when in function 25) .…”
Section: Discussionsupporting
confidence: 82%
“…Regis et al (2011) found that the incorporation of 0.6% antimicrobial MUPB reduced the base's hardness, in agreement with the results of the current study. That said, our results are in opposition to a study in which alumina was added to the PMMA, which had a positive impact on the latter's physical and mechanical properties (Arora et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Compagnoni et al (2014) studied the effect of antimicrobial polymer (poly[2-tertbutylaminoethyl] methacrylate [PTBAEMA]) on the surface roughness and found that the addition of PTBAEMA to a PMMA acrylic denture base increased the Ra values, which is in line with the results of the current study. Meanwhile, Regis et al (2011) showed that the use of antimicrobial monomer methacryloyloxyundecylpyridinium bromide (MUPB) had no effect on the roughness of polished acrylic resin. Another team used alcohol vinegar in the PMMA as a way to reduce the number and adhesion of Candida albicans specimens; this had no effect on the surface roughness of the PMMA (de Castro et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations